1991
DOI: 10.1002/jlb.50.4.373
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Human Neutrophils to and Activation by Type-I Collagen Involving a β2 Integrin

Abstract: We previously demonstrated that the alpha 1(I) polypeptide chain of collagen can bind and activate polymorphonuclear neutrophils (PMN). In the present experiments, performed in culture grade 96-well plastic plates coated with collagen, fibronectin, or other proteins, adhesion was assessed by staining the adhering cells after 30 min with crystal violet and measuring absorbance at 560 nm, and activation of PMNs was assessed by measuring the amount of O2-formed. Adhesion occurred at 17 and 37 degrees C but activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 14 publications
1
38
0
Order By: Relevance
“…During these processes, cells exchange various messages, principally through cytokine production, some of them being triggered by interactions with ECM proteins, that in turn lead to the maintenance of an inflammatory state or, on the contrary, to the restoration of physiological conditions. Previous works of our laboratory have shown that type I collagen was able to deeply influence the metabolism of cells involved in these processes, in the case of fibroblasts (22,23) as well as PMNs (3)(4)(5)(6). In this work, we present new evidences that type I collagen interactions with monocytes are critical events involved in these processes.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…During these processes, cells exchange various messages, principally through cytokine production, some of them being triggered by interactions with ECM proteins, that in turn lead to the maintenance of an inflammatory state or, on the contrary, to the restoration of physiological conditions. Previous works of our laboratory have shown that type I collagen was able to deeply influence the metabolism of cells involved in these processes, in the case of fibroblasts (22,23) as well as PMNs (3)(4)(5)(6). In this work, we present new evidences that type I collagen interactions with monocytes are critical events involved in these processes.…”
Section: Discussionmentioning
confidence: 50%
“…A total of 100 l of the Ab solution at the appropriate titer (6 g IgG/ml) was added to 1.5 ϫ 10 6 monocytes in 900 l Dulbecco's solution containing 1.3 mM CaCl 2 and 1 mM MgCl 2 . Microtubes were shaken horizontally at 150 cycles/min for 90 min at 37°C (5,15). Monocyte adhesion and O 2 Ϫ production on collagen I were then evaluated as described above, in the continuous presence of mAbs in the incubation medium.…”
Section: Effect Of Anti-integrin Mabs On Monocytesmentioning
confidence: 99%
“…7, the distribution of BAP31 and CD11b/CD18 in resting PMN is quite similar. Both proteins mainly localized to secondary granule-enriched fractions (17)(18)(19)(20) with only a minor fraction of protein colocalizing with plasma membrane-enriched fractions (11)(12)(13)(14)(15). After stimulation with fMLP (10 Ϫ7 M, 30 min), there was significant redistribution of BAP31 from cellular granule-enriched fractions (particularly secondary granules) to plasma membraneenriched fractions similar to that observed for CD11b/CD18.…”
Section: Bap31 Associates With Cd11b/cd18mentioning
confidence: 58%
“…On the other hand, some types of mobile cells also interact with collagens, for instance polymorphonuclear neutrophils (PMN), 1 a variety of leukocytes circulating in blood, capable of crossing the vascular wall in order to invade the inflamed tissues and to participate in defenses against bacteria or foreign molecules through their property of phagocytosis. In several previous papers, we demonstrated that PMN and type I collagen do interact and began to describe their interactions (3)(4)(5).…”
mentioning
confidence: 99%